10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Despite progress in leprosy control, delayed diagnosis remains a barrier to achieving Zero Leprosy, particularly in low-endemic settings. Diagnostic delay not only sustains hidden transmission but also leads to preventable disability and lifelong consequences for affected individuals. Pakistan, although classified as low endemic, continues to report a high proportion of new leprosy cases presenting with grade 2 disability (G2D), indicating delays in case detection. This study explored the reasons for delayed leprosy diagnosis in Pakistan and participant-suggested strategies to reduce delay, from the perspective of persons presenting with visible disability. A qualitative study was conducted using semi-structured interviews with persons affected by leprosy who presented with G2D at diagnosis. Participants were recruited through leprosy service providers in Pakistan. Interviews explored care-seeking pathways, experiences with the health system, stigma, and perceived barriers to timely diagnosis. Audio-recorded interviews were transcribed and analysed using thematic analysis, with attention to the interpreter-mediated nature of some participant accounts. Participants described prolonged diagnostic pathways marked by repeated healthcare visits, misdiagnosis, inappropriate treatment, and referrals between multiple providers before receiving a leprosy diagnosis. Limited awareness of leprosy among the public and frontline healthcare workers was a contributor to delay. Stigma emerged as both a cause and a consequence of delayed diagnosis, influencing disclosure, care-seeking behaviour, and social interactions. Structural barriers, fragmented service provision, financial constraints, and the absence of a national leprosy control programme, further compounded delays, resulting in diagnosis only after the onset of visible deformities. Diagnostic delay in Pakistan is driven by intersecting individual, social, and health system factors and remains an obstacle to preventing disability and interrupting transmission. From a Zero Leprosy perspective, reducing diagnostic delay is a clinical, programmatic and ethical imperativ. Strengthening awareness, improving health worker training, decentralising diagnostic services, and integrating person-centred psychosocial support can advance early detection and disability prevention.